Frontispiece: Finding the Most Catalytically Active Platinum Clusters With Low Atomicity. Issue 34 (10th August 2015) - Imaoka, Takane; Kitazawa, Hirokazu; Chun, Wang‐Jae; Yamamoto, Kimihisa
Abstract : Cluster Compounds The atomicity of subnanometer platinum clusters significantly influences their catalytic activity. In their Communication on page 9810 ff., K. Yamamoto et al. report Pt19 as the most catalytically active species for oxygen reduction.